Floodplain downed wood volumes: a comparison across three biomes. Issue 8 (28th November 2016) - Lininger, Katherine B.; Wohl, Ellen; Sutfin, Nicholas A.; Rose, Joshua R.
Abstract: Downed large wood (LW) in floodplains provides habitat and nutrients for diverse organisms, influences hydraulics and sedimentation during overbank flows, and affects channel form and lateral migration. Very few studies, however, have quantified LW volumes in floodplains that are unaltered by human disturbance. We compare LW volumes in relatively unaltered floodplains of semiarid boreal lowland, subtropical lowland, and semiarid temperate mountain rivers in the United States. Average volumes of downed LW are 42.3 m 3 ha −1, 50.4 m 3 ha −1, and 116.3 m 3 ha −1 in the semiarid boreal, subtropical, and semiarid temperate sites, respectively. Observed patterns support the hypothesis that the largest downed LW volumes occur in the semiarid temperate mountain sites, which is likely linked to a combination of moderate‐to‐high net primary productivity, temperature‐limited decomposition rates, and resulting slow wood turnover time. Floodplain LW volumes differ among vegetation types within the semiarid boreal and semiarid temperate mountain regions, reflecting differences in species composition. Lateral channel migration and flooding influence vegetation communities in the semiarid boreal sites, which in turn influences floodplain LW loads. Other forms of disturbance such as fires, insect infestations, and blowdowns can increase LW volumes in the semiarid boreal and semiarid temperate mountain sites, where rates of wood decay are relatively slow compared with the subtropical lowland sites. Although sediment is the largest floodplain carbon reservoir, floodplain LW stores substantial amounts of organic carbon and can influence floodplain sediment storage. In our study sites, floodplain LW volumes are lower than those in adjacent channels, but are higher than those in upland (i.e. non‐floodplain) forests. Given the important ecological and physical effects of floodplain LW, efforts to add LW to river corridors as part of restoration activities, and the need to quantify carbon stocks within river corridors, we urge others to quantify floodplain and instream LW volumes in diverse environments. Copyright © 2016 John Wiley & Sons, Ltd.